Side‐chain crystallization and phase transition of poly[styrene‐co‐(maleic anhydride)]‐g‐alkylamine comb‐like polymers. Issue 1 (20th August 2021) - Mao, Huiqin; Wang, Yanpeng; Wang, Haixia; Li, Lang; Shi, Haifeng
Abstract: Taking NHCO as the chemical spacer, poly[styrene‐ co ‐(maleic anhydride)]‐ g ‐alkylamine (SMAC n N) comb‐like polymers are prepared through grafting reaction between poly[styrene‐ co ‐(maleic anhydride)] and n ‐alkylamine with n changing from 12 to 18. SMAC n N comb‐like polymers present an obvious crystallization behavior owing to the introduced alkyl side chains, and the melting temperature and enthalpy of the side‐chain crystallites increase from 9.2 to 41.6 °C and from 6.0 to 17.6 kJ mol −1, respectively, showing a variation with the side‐chain length. At least 12 side‐chain carbon atoms are required to pack into a hexagonal crystal structure for SMAC n N comb‐like polymers. Fourier transform infrared and X‐ray analysis results demonstrate the phase transition from hexagonal to an amorphous state, and the conformationally disordered alkyl chains affect the packing manner of side‐chain crystallites. Including the side‐chain length and polymer backbone, the chemical spacer between the side chain and the main chain influences the formation of side‐chain crystallites and the phase transition process. So, the study of SMAC n N further strengthens the understanding of the phase transition behavior and side‐chain crystallization of comb‐like polymers triggered by the side‐chain length and the microstructure differences. © 2021 Society of Industrial Chemistry. Abstract : Side‐chain packing manner and crystallization habits depend on the polymer backbone, side‐chain length and chemical spacer.